Studi Komparatif Konsep Tauhid dalam Mazhab Sunni dan Syiah: Analisis Teologis - Lutfi Ahmad Mutorik; Disyela Apriswa Mandai; Sofa Nur Alfiah; Muhammad Raka Iqbal Fadil Muharom; Rifky Ali Perdiansyah; Muhammad Dzaky Maulana Putra; Dadan Firdaus (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to comparatively analyze the concept of tawhid in Sunni and Shi'a Imamiyyah schools from a theological perspective. Using an exploratory qualitative approach and literature study method, this research examines the theological structures of both traditions, identifying points of convergence and key differences in their understanding of God's oneness. The findings reveal that although both traditions uphold tawhid as the core of faith, differing epistemological approaches and authoritative frameworks lead to significant distinctions. The Sunni tradition emphasizes three dimensions of tawhid—rububiyyah, uluhiyyah, and asma’ wa sifat—while the Shi’a Imamiyyah integrates the concept with the doctrines of imamah and walayah. The study further highlights that such theological diversity can enrich Islamic intellectual tradition and foster constructive inter-sectarian dialogue when managed inclusively. The research recommends promoting sectarian tolerance education and inter-traditional dialogue as key strategies to enhance Islamic unity.